Proses Kreatifitas Penciptaan Original Soundtrack pada Teater Musikal Wahyu Psikadelika Karya Nanda Darius - Denis Setiaji; Emmanuel Yefta Irvanda (FKIP, Universitas Palangka Raya, 2025)
This research aims to find out in depth about the creative process carried out by the director and also the composer in making OST in the Wahyu Psikapdelika musical theater, using a qualitative approach method, namely ethnography with Wallas's concept theory (1926), using 4 stages of the inner process consisting of preparation, incubation, enlightenment, and verification. Data collection in this study used interview techniques, observation, data analysis, and documentation as concrete evidence of the existence of this research using Wallas' conceptual foundation. This research aims to find new ideas about how a director's creative process makes OST with his epic mystagogia method. The results of this study will discuss what processes are needed in making the original soundtrack in the Wahyu Psikapdelika script, several pieces of verse that are not mature and have not been made into a song or OST, then presented several pieces of sheet music containing arrangements and compositions resulting from the making of OST, then the techniques used in the process. It can be concluded that the creative process in this research produces an idea that is contained in the original soundtrack or OST which is used to support the aspects of theme and atmosphere in Wahyu Psikapdelika Musical Theater.